Estimation and determinants of Chinese banks' total factor efficiency: A new vsion based on unbalanced development of Chinese banks and their overall risk - Shiyi Chen; Wolfgang Karl Härdle; Li Wang (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2014)
The development of shadow banking system in China catalyzes the expansion of banks' off-balance-sheet activities, resulting in a distortion of China's traditional credit expansion and underestimation of its commercial banks' overall risk. This paper is the first to incorporate banks' overall risk, endogenously into bank's production process as undesirable by-product for the estimation of banks' total factor efficiency (TFE) as well as TFE of each production factor. A unique data sample of 171 Chinese commercial banks, which is the largest data sample concerning with Chinese banking efficiency issues until now as far as we know, making our results more convincing and meaningful. Our results show that, compared with a model incorporated with banks' overall risk, a model considering on-balance-sheet lending activities only may over-estimate the overall average TFE and under-estimate TFE volatility as a whole. Higher overall risk taking of banks tends to decrease bank TFE through 'diverting effect'. However, significant heterogeneities of bank integrated TFE (TFIE) and TFE of each production factor exist among banks of different types or located in different regions, as a result of still prominent unbalanced development of Chinese commercial banks today. Based on newly estimated TFIE, the paper also investigates the determinants of bank efficiency, and finds that a model with risk-weighted assets as undesirable outputs can better capture the impact of shadow banking involvement.
Keywords: C14; C33; G21; 330; Total Factor Efficiency; Unbalanced Development; Shadow Banking; Global SBM